Social support as a determinant of psychosocial wellbeing of women with infertility in Ibadan, Oyo state.
Infertility is a painful scenario, which influences women socially and mentally, leaving them in a terrible life situation. This study explored the impact of social support on the mental well-being of women experiencing infertility in Oyo state and Ibadan. The study employed a descriptive survey research approach and simple random sampling to choose 150 women visiting reproductive clinics at Adeoyo and Ring Road state hospitals in Ibadan. The age range of the participants ranges between 18 and 50years old. A standardized questionnaire was drawn from the Social Support Questionnaire of Copenhagen, which was developed by the Psychosocial Department, National Institute of Occupational Health, Copenhagen, Denmark in 2003, Ryf’s Psychological Wellbeing Scale, and the Social Wellbeing Scale developed by Lee Keyes (2013). The reliability of the instruments is: financial support (r = 0.74), information access (r = 71) and companionship support (r = 72). Descriptive statistics was used to analyse data. The hypotheses were tested with the use of Analysis of Variance (ANOVA). The result showed there was a significant effect of financial support on the social wellbeing of women with infertility in Ibadan (F = 10.801, p (.000) .05). There was signifìcant effect of access to information on the social wellbeing of women with infertility in Ibadan (F = 4.4114, p (.000) .05). Furthermore, a signifìcant effect of companion support on the psychological wellbeing of women with infertility in Ibadan was reported. (p (.000).05, F = 7.346). The study recommends that medical social workers should ensure the provision of psychosocial support Services for couples experiencing infertility.